(3QSGdI JbdjO GdedJbi JbdjOkG Ues - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3EYde habc Gdehdi hefMc SHjd GdgOi ef bGFe GdReGf gGOi GdeSJLjHjf GdefJbe ef GdeTQcjf hGdeGQbjf s
(3BNQgG (B:s
(3Ydi JhGJQ fYeg hGcJH GdejKGb Ydi GdeSJLjHjf HVHW GdMdjI hCMcGe GdTgGOI hcf Hge QajbkG hfYe GdfUjQ GdeYjf SHMGfg hMOg dGTQjc dg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B23s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3abg GdePGgH GdCNQis